Perancangan Aplikasi Penjualan Barang Pada Bedink Mattress Store - Wike Rahayu; Anzal Fadly Hadi Pratama; Yusri Nuraeni; Thoyyibah T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Bedink Mattress Store is a company engaged in trading business. Bedink Mattress Store sells room equipment such as spring beds, rolled mattresses, sofas and pillows. In carrying out product sales activities, the company still uses manual data processing and has not yet used one of the web-based technology software, namely e-commerce. The research conducted by the author aims to create a website-based application for selling household equipment at the Bedink Mattress Store. This information system was created using the Waterfall method and was built using HTML, Javascript, Node.js, Express.js, React.jc and mongoDB languages. The results of developing this sales application can be used practically and effectively in the sales process and can be used as promotional media.